A Review of Hydrogen Sulfide Synthesis, Metabolism, and Measurement: Is Modulation of Hydrogen Sulfide a Novel Therapeutic for Cancer? - Cao, Xu; Ding, Lei; Xie, Zhi-Zhong; Yang, Yong; Whiteman, Matthew; Moore, Philip K; Bian, Jin-Song (Antioxidants & redox signaling, 2019)
Hydrogen sulfide (H S) has been recognized as the third gaseous transmitter alongside nitric oxide and carbon monoxide. In the past decade, numerous studies have demonstrated an active role of H S in the context of cancer biology. The three H S-producing enzymes, namely cystathionine γ-lyase (CSE), cystathionine β-synthase (CBS), and 3-mercaptopyruvate sulfurtransferase (3MST), have been found to be highly expressed in numerous types of cancer. Moreover, inhibition of CBS has shown anti-tumor activity, particularly in colon cancer, ovarian cancer, and breast cancer, whereas the consequence of CSE or 3MST inhibition remains largely unexplored in cancer cells. Intriguingly, H S donation at high amounts or a long time duration has also been observed to induce cancer cell apoptosis and while sparing noncancerous fibroblast cells. Therefore, a bell-shaped model has been proposed to explain the role of H S in cancer development. Specifically, endogenous H S or a relatively low level of exogenous H S may exhibit a pro-cancer effect, whereas exposure to H S at a higher amount or for a long period may lead to cancer cell death. This indicates that inhibition of H S biosynthesis and H S supplementation serve as two distinct ways for cancer treatment. This paradoxical role of H S has stimulated the enthusiasm for the development of novel CBS inhibitors, H S donors, and H S-releasing hybrids. A clear relationship between H S level and cancer progression remains lacking. The possibility that the altered levels of these byproducts have influenced the cell viability of cancer cells has not been excluded in previous studies when modulating H S producing enzymes. The consequence of CSE or 3MST inhibition in cancer cells need to be examined in the future. Better portrayal of the crosstalk among these gaseous transmitters may not only lead to an in-depth understanding of cancer progression but also shed light on novel strategies for cancer therapy.